Linking restless legs syndrome with Parkinson's disease: clinical, imaging and genetic evidence - Peeraully Tasneem; Tan Eng-King (Translational Neurodegeneration, 2012)
Abstract Restless legs syndrome (RLS) and Parkinson's disease (PD) are both common neurological disorders. There has been much debate over whether an etiological link between these two diseases exists and whether they share a common pathophysiology. Evidence pointing towards a link includes response to dopaminergic agents in PD and RLS, suggestive of underlying dopamine dysfunction in both conditions. The extrastriatal dopaminergic system, in particular altered spinal dopaminergic modulation, may be variably involved in PD patients with RLS symptoms. In addition, there is now evidence that the nigrostriatal system, primarily involved in PD, is also affected in RLS. Furthermore, an association of RLS with the parkin mutation has been suggested. The prevalence of RLS has also been reported to be increased in other disorders of dopamine regulation. However, clinical association studies and functional imaging have produced mixed findings. Conflicting accounts of emergence of RLS and improvement in RLS symptoms after deep brain stimulation (DBS) also contribute to the uncertainty surrounding the issue. Among the strongest arguments against a common pathophysiology is the role of iron in RLS and PD. While elevated iron levels in the substantia nigra contribute to oxidative stress in PD, RLS is a disorder of relative iron deficiency, with symptoms responding to replacement therapy. Recent ultrasonography studies have suggested that, despite overlapping clinical features, the mechanisms underlying idiopathic RLS and RLS associated with PD may differ. In this review, we provide a concise summary of the clinical, imaging and genetic evidence exploring the link between RLS and PD.